Strategi Dakwah Takmir Masjid Raya Al-Falah Sragen dalam Membina Generasi Muda - Khuzaemah, Siti; Zaini, Ahmad (IAIN Madura, 2022)
This paper aims to discuss how the strategy of preaching takmir of Masjid Raya al-Falah in fostering the younger generation. This research is a field study with a qualitative approach which will be carried out in 2021 at the Al-Falah Grand Mosque, Sragen. The primary data source in this research is direct interviews with the mosque takmir. The sources of the interview came from the takmir of the mosque, mosque administrators, mosque employees and courtiers of Masjid Raya al-Falah Sragen. In addition to interviews, data were obtained through observation by observing, recording, listening, photographing, recording, and directly following the various activities that were the busiest at the Al-Falah Mosque, Sragen. The results of the study show that the strategy of preaching takmir mosques in developing and fostering the younger generation is to conduct youth development in mosques.